Therapeutic approaches to CNS diseases via the meningeal lymphatic and glymphatic system: prospects and challenges - Zhang, Rui; Li, Jiuhong; Li, Xueying; Zhang, Si (Frontiers in Cell and Developmental Biology, 2024)
The brain has traditionally been considered an 'immune-privileged' organ lacking a lymphatic system. However, recent studies have challenged this view by identifying the presence of the glymphatic system and meningeal lymphatic vessels (MLVs). These discoveries offer new opportunities for waste clearance and treatment of central nervous system (CNS) diseases. Various strategies have been developed based on these pathways, including modulation of glymphatic system function, enhancement of meningeal lymphatic drainage, and utilization of these routes for drug delivery. Consequently, this review explores the developmental features and physiological roles of the cerebral lymphatic system as well as its significance in various CNS disorders. Notably, strategies for ameliorating CNS diseases have been discussed with a focus on enhancing glymphatic system and MLVs functionality through modulation of physiological factors along with implementing pharmacological and physical treatments. Additionally, emphasis is placed on the potential use of the CNS lymphatic system in drug delivery while envisioning future directions in terms of mechanisms, applications, and translational research.